2015
DOI: 10.3389/fendo.2015.00019
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Deprivation and the Cellular Response to Hypoxia in Adipocytes – Perspectives on White and Brown Adipose Tissues in Obesity

Abstract: Relative hypoxia has been shown to develop in white adipose tissue depots of different types of obese mouse (genetic, dietary), and this leads to substantial changes in white adipocyte function. These changes include increased production of inflammation-related adipokines (such as IL-6, leptin, Angptl4, and VEGF), an increase in glucose utilization and lactate production, and the induction of fibrosis and insulin resistance. Whether hypoxia also occurs in brown adipose tissue depots in obesity has been little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 89 publications
(128 reference statements)
0
65
1
2
Order By: Relevance
“…One of the mechanisms that trigger the accumulation of extracellular matrix components is adipose tissue hypoxia, which ultimately leads to fibrosis (115). Hypoxia in adipose tissue results in the stabilization of hypoxiainducible factor 1␣ (HIF-1␣), which in turn induces the expression of fibrotic proteins such as lysyl oxidase (LOX), elastin, collagen I and III, tissue inhibitor of matrix metalloproteinase-1 (TIMP-1), and connective tissue growth factor (CTGF) (115,317). In this sense, obese subjects exhibit reduced elastin and increased collagen I, III, V, and VI, and CTGF in adipose tissue, with visceral fat showing more fibrotic strokes than subcutaneous adipose tissue (61,301,302).…”
Section: Recruitment Of Proinflammatory Immune Cells In Obesity Perpementioning
confidence: 99%
“…One of the mechanisms that trigger the accumulation of extracellular matrix components is adipose tissue hypoxia, which ultimately leads to fibrosis (115). Hypoxia in adipose tissue results in the stabilization of hypoxiainducible factor 1␣ (HIF-1␣), which in turn induces the expression of fibrotic proteins such as lysyl oxidase (LOX), elastin, collagen I and III, tissue inhibitor of matrix metalloproteinase-1 (TIMP-1), and connective tissue growth factor (CTGF) (115,317). In this sense, obese subjects exhibit reduced elastin and increased collagen I, III, V, and VI, and CTGF in adipose tissue, with visceral fat showing more fibrotic strokes than subcutaneous adipose tissue (61,301,302).…”
Section: Recruitment Of Proinflammatory Immune Cells In Obesity Perpementioning
confidence: 99%
“…So, our perception is that in white adipose tissue (WAT) low oxygen (hypoxia) are the case as outlined in the research article of [24] and the review of [25]. We stated earlier and depicted in Figure 1 that in WAT ischemic and/or hypoxic conditions may occur.…”
Section: Hypoxia Results In Further Fat Synthesis and Tumor Growthmentioning
confidence: 94%
“…Second, lipolysis can be effectively pharmacologically modulated (27) (e.g., by acipimox). Finally, sustained adipose tissue hypoxia or activation of hypoxia-regulated signaling pathways can stimulate lipolysis (18,28,29); however, it is worth noting that IH exposure is characterized by distinct cellular and molecular features, which are different from exposure to sustained hypoxia (30,31). Using glycerol release and adipocyte size distribution as functional and morphological indices of adipocyte lipolysis, this study showed that IH exposure stimulated basal lipolysis, thus providing a functional explanation for results seen in previous studies that reported increased plasma FFA levels in patients with OSA and rodents exposed to IH (7,25,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue O 2 levels as low as 15 mm Hg have been seen to develop in adipose tissue as adipocyte size increases in obese humans and rodents (17). Lowered tissue O 2 levels have been reported to increase lipolysis, decrease adipogenesis, alter the profile of secreted adipokines, and induce insulin resistance in adipose tissue (18). In contrast to the sustained adipose tissue hypoxia found in obesity, OSA is characterized by repetitive drops in arterial O 2 levels that induce tissue-specific changes in oxygenation in various organs (19).…”
mentioning
confidence: 99%